IMPLEMENTASI PROGRAM PENGEMBANGAN PERIKANAN TANGKAP DALAM PENGEMBANGAN EKONOMI NELAYAN DI DESA GOISOOINAN, KECAMATAN SIPORA UTARA, KABUPATEN KEPULAUAN MENTAWAI - Rosadi Sinaga, Duddy Agus; Indraddin, Indraddin; Elfitra, Elfitra (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
The Mentawai Islands District Government seeks to develop capture fisheries by implementing fisheries motorization policies to make fishermen change from fishermen peasants (oriented to meeting their daily needs) to become fishermen post-peasants (using fishing technology in the form of outboard motors or motor boats). This research tries to answer the problems faced in the implementation of capture fisheries development programs in Goisooinan Village, North Sipora District, Mentawai Islands Regency. This study uses a qualitative approach. The researcher used structuration theory from Anthony Giddens which focused on fishermen as agents who had knowledge and awareness of practical awareness, discursive awareness and unconscious motivation caused by the existence of rules and resources that could empower and curb fishermen in taking action. From the results of the study, it was found that the issue of the capture fisheries program was the distribution and utilization of fisheries fishing equipment in the form of 5 pk motorcycles which were not targeted, most fishermen not only used the machine to catch fish but also for other activities such as transporting sand from the sea and going to the fields, the economic structure of an agrarian society, the limitations of fishing gear, the high price of fuel, the limited human resources of fishermen, no assistance and supervision of fishermen, and bad weather conditions.